Prognostic impact of chronic kidney disease and renal replacement therapy in ventricular tachyarrhythmias and aborted cardiac arrest - Weidner, Kathrin; Behnes, Michael; Schupp, Tobias; Rusnak, Jonas; Reiser, Linda; Taton, Gabriel; Reichelt, Thomas; Ellguth, Dominik; Engelke, Niko; Kern-Bollow, Armin; El-Battrawy, Ibrahim; Ansari, Uzair; et al. (Clinical research in cardiology, 2019)
BACKGROUND: The study sought to assess the prognostic impact of chronic kidney disease (CKD) and renal replacement therapy (RRT) in patients with ventricular tachyarrhythmias and sudden cardiac arrest (SCA) on admission. - METHODS: A large retrospective registry was used including all consecutive patients presenting with ventricular tachycardia (VT), fibrillation (VF) and SCA on admission from 2002 to 2016. Non-CKD vs. "CKD without RRT", and "CKD without RRT" vs. "CKD with RRT" were compared applying multivariable Cox regression models and propensity-score matching for evaluation of the primary prognostic endpoint defined as long-term all-cause mortality at 2 years. Secondary prognostic endpoints were cardiac death at 24 h, in-hospital death at index and the composite endpoint of recurrent ventricular tachyarrhythmias, appropriate ICD therapies and cardiac death at 24 h. - RESULTS: In 2686 unmatched high-risk patients with ventricular tachyarrhythmias and SCA, non-CKD was present in 46%, "CKD without RRT" in 46% and "CKD with RRT" in 8%. Each, VT and VF occurred in about one-third of CKD patients. Multivariable Cox regression models revealed that "CKD without RRT" (HR = 2.118; p = 0.001) and "CKD with RRT" (HR = 3.043; p = 0.001) patients were associated with the primary endpoint of long-term mortality at 2 years, which was also proven after propensity-score matching (non-CKD vs. "CKD without RRT": 43% vs. 27%, log rank p = 0.001; HR = 1.847; "CKD without RRT" vs. "CKD with RRT": 74% vs. 51%, log rank p = 0.001; HR = 2.129). The rates of secondary endpoints were higher for cardiac death at 24 h, in-hospital death at index and the composite of recurrent ventricular tachyarrhythmias, appropriate ICD therapies and cardiac death at 24 h, respectively, for "CKD without RRT" and "CKD with RRT" patients. CONCLUSION: In patients presenting with ventricular tachyarrhythmias and aborted SCA on admission, the presence of CKD, especially combined with RRT, is independently associated with an increase of long-term all-cause mortality at 2 years, cardiac death at 24 h, in-hospital death and the composite of recurrent ventricular tachyarrhythmias, appropriate ICD therapies and cardiac death at 24 h.
First online: 21 December 2018
Gesehen am 02.07.2019